Remineralization evaluation of cocos nucifera extracts via element quantification - Rahamat, Siti Fatimah; Wan Abd. Manan, Wan Nor Hayati; Abllah, Zurainie (Atlantis Press, 2018)
Demineralization causes plaque calcium (Ca) to dissolve out from the enamel. Prolonged condition would allow enamel caries to worsen. To reverse the condition via remineralization, abundant of free available Ca and phosphorus (P) in the saliva are required. Thus, daily diet with high Ca and P content are important to ensure the continuous supply of Ca and P. Being one of Malaysia's major component of medical applications and daily consumptions, virgin coconut oil (VCO), coconut milk (CM), and coconut water (CW) are yet to be discovered their mineral content especially Ca and P. Hence, this study aims to evaluate the Ca and P content in VCO, CM, and CW. Inductive coupled plasma-mass spectrometry (ICP-MS) was used in analyzing the Ca and P content in VCO, CM, and CW. After acid digestion (Method 3051a) using Teflon vessels under 170°C, the samples were diluted and the readings were compared. The Ca concentration in descending order VCO (0.47±0.15), CW (0.45±0.05) and CM (0.44±0.15), while P concentration in descending order is as follows CM (0.25±0.05), CW (0.09±0.05), and VCO (0.05±0.06). With no huge difference in Ca content, CM is considered to exhibit a high Ca and P content in total. In conclusion, CM exhibits a promising remineralization potential on enamel caries with high Ca and P content.